Some basic problems concerning world animal production at the beginning of the XXI century - Horn, Péter (Acta Agraria Debreceniensis, 2012)
The author summarizes the main new challenges facing animal agriculture: growing GDP in many countries increasing animal protein demand, bioenergy industry as a new player using potential food or feedstuffs, increasing demand, Growing water and land scarcity, weaking the position of plant agriculture, feed production. Forecasts are summarized regarding the magnitude of meat consumption increases, and the possible plant biomass quantities required additionally in the next 20 years to cover the needs of food, feed and biofuel on a global scale. Efficiencies of various animal production sectors, poultry, pork, beef, mutton meat, milk and eggs and their environmental footprints are compared, summarizing the most important research results concerning UK, USA, OECD evaluations. Intensive systems using highly productive plant and animal population will play an even more important role in the future especially in poultry, pig, milk and aquaculture production system being efficient users of resources (feed, water, land) and the environmental foot print is smaller per unit product.